2009
DOI: 10.1111/j.1525-139x.2009.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Complication Rates and Survival of Peritoneal Dialysis Catheters: The Role of Percutaneous Versus Surgical Placement

Abstract: Considerable controversy currently exists in the literature concerning the mode of catheter placement and its impact on the technical success of peritoneal dialysis (PD). We decided to compare the impact of the surgical versus the percutaneous insertion technique on peritoneal dialysis catheter (PDCs) complications and survival. Our study population comprised 152 patients in whom 170 PDCs were inserted between January 1990 and December 2007 at the main PD unit on the island of Crete. Eighty four catheters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 28 publications
1
51
1
Order By: Relevance
“…Selection bias, previous laparotomy, operator expertise, catheter type (coiled vs straight) and, in the case of peritonitis, other patient-related factors are all potential confounders that may have affected outcomes in these retrospective studies. Dialysate leakage was seen more frequently in the percutaneous insertion groups in some studies (8)(9)(10)15,22); other studies showed no difference between the two groups (6,7,11,13). The higher incidence of leakage associated with percutaneous placement may be partly attributed to a shorter break-in period (time from insertion to use of catheter) in the percutaneous insertion groups (8,9,15,22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Selection bias, previous laparotomy, operator expertise, catheter type (coiled vs straight) and, in the case of peritonitis, other patient-related factors are all potential confounders that may have affected outcomes in these retrospective studies. Dialysate leakage was seen more frequently in the percutaneous insertion groups in some studies (8)(9)(10)15,22); other studies showed no difference between the two groups (6,7,11,13). The higher incidence of leakage associated with percutaneous placement may be partly attributed to a shorter break-in period (time from insertion to use of catheter) in the percutaneous insertion groups (8,9,15,22).…”
Section: Discussionmentioning
confidence: 99%
“…Excluding those two outlying cohorts in whom 1-year catheter survival was only 33-36%, the average survival of catheters inserted using the percutaneous technique in the literature was 80% at 12 months following insertion. Percutaneously inserted catheters also appear to fare well in terms of overall complication rates with some studies showing a reduced peritonitis rate (6,8,15) and other studies showing no significant differences in peritonitis rates between the two insertion groups (7,11). Similarly, no difference in incidence of unresolved drainage failure was seen between the two groups in most studies that compared the 2 techniques (7-9,11,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perakis et al reported 170 PD catheter insertions (86 percutaneous) where a higher incidence of leak occurred in the percutaneous group (10% vs 2%). However, infectious complications were higher in the surgical group (25). A trial from Iran randomized 64 patients to surgical or percutaneous insertion and found a higher incidence of outflow failure and hemoperitoneum in the surgical group.…”
Section: Methodsmentioning
confidence: 99%